Analysis of Vitamin C and Calcium in Jongi Fruits (Dillenia serrata Thunb) Based on Their Maturity Level - Miryam B. Kalase; Daud K. Walanda; Mery Napitupulu (Jurnal Akademika Kimia, 2019)
Jongi plant (Dillenia serrata Thunb) is one of the plants that found  Poso District. The characteristics of this fruit are mainly on the refreshing sour taste and attractive color which is yellow. This study aims to determine the levels of vitamin C and calcium in this fruit based on the level of maturity. The fruit of jongi used as a sample was categorized into there type of maturity namely mature, ripe, and overripe. The method used for vitamin C analysis was iodimetry and for calcium, analysis using spectrophotometry (λ: 422.7 nm). From the results of the analysis, it was obtained that the levels of vitamin C in fruit jongi successively were 81.84, 114.40, and 70.40 mg/100 g, while the calcium levels obtained in the fruits were 5.91, 5.65, and 6.46 mg/100 g. The data above showed that the maximum vitamin C content in jongi fruit when the fruit was in ripe type, while the highest calcium content in jongi fruit was when the fruit in overripe type.